Family oblige: the link between CSR and succession intention in small and medium family firms - Andrea Stübner; Svenja Jarchow (Journal of Business Economics, 2022)
This study investigates how family continuation, namely family tradition and succession intention, alter the socially responsible behavior of small and medium sized (SME) family firms. Using a unique dataset, we have conducted multiple regressions on survey data from German family SMEs and show a statistically and economically significant increase in Corporate Social Responsibility (CSR) alongside the planning of family succession. However, when analyzing the different facets of CSR, we have found strong variances: While succession intention goes along with an increased community, market, and supply chain engagement this is not the case for CSR directed towards employees, or the environment. Family tradition didn't correlate with a change in CSR behaviour to a relevant extent. In our theoretical embedding we employed socio-emotional wealth (SEW) theory to explain our findings. Thereby, our study fills a gap in the literature adding the perspective of SME family firms on the use of CSR in the context of family succession and also adding to the theoretical understanding of SEW.
Keywords: M14; G32; D22; D64; 650; CSR; SME; SEW; Family firm succession